EVALUASI PELAKSANAAN PEMBELAJARAN PEMELIHARAAN MESIN SEPEDA MOTOR KELAS XI DENGAN MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) DI SMK NEGERI NGARGOYOSO - Nina Intan Saputri; Ranto Ranto; Suharno Suharno (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The purpose of this research is to evaluate the implementation of motorcycle engine maintenance learning at Ngargoyoso Vocational High School. The evaluation in this study uses the CIPP model (context, input, process, product). The location of this research is in Ngargoyoso Vocational High School on learning to maintain class XI motorcycle engines with research subjects as teachers of maintenance for motorbike engines in class XI, students of class XI, and facilities. The technique of collecting data used a questionnaire that was distributed to class XI TSM A, XI TSM B, and XI TSM C and the teacher of motorcycle engine maintenance. Interview with one of the teachers, and document the final value of maintaining a XI class motorcycle engine. The validity used in this study is content validity where validation is carried out by experts. The trial of the research instrument was conducted in class XI of TSM D Ngargoyoso State Vocational School by testing the validity of using SPSS. Analysis of scores using the average to be assessed based on the assessment criteria. The results of the study show: (1) evaluation of the context (context) which includes the background of the program has been classified as good; (2) evaluation of input (input) is classified as good, input aspects include: human resources, curriculum, learning resources, and infrastructure; (3) evaluation of the process (process) which includes the process of implementing learning in classrooms and workshops is classified as good, but the aspects of the learning media used are quite sufficient so that they need to be improved. (4) Evaluation of product (product), which is the final grade of students classified as good.